The significance of pyrogenic polycyclic aromatic hydrocarbons in Borneo peat core for the reconstruction of fire history. - Sher-Rine Kong (Public Library of Science (PLoS), 2021)
The reconstruction of fire history is essential to understand the palaeoclimate and human history. Polycyclic aromatic hydrocarbons (PAHs) have been extensively used as a fire marker. In this work, the distribution of PAHs in Borneo peat archives was investigated to understand how PAHs reflect the palaeo-fire activity. In total, 52 peat samples were analysed from a Borneo peat core for the PAH analysis. Pyrogenic PAHs consist of 2-7 aromatic rings, some of which have methyl and ethyl groups. The results reveal that the concentration of pyrogenic PAHs fluctuated with the core depth. Compared to low-molecular-weight (LMW) PAHs, the high-molecular-weight (HMW) PAHs had a more similar depth variation to the charcoal abundance. This finding also suggests that the HMW PAHs were mainly formed at a local fire near the study area, while the LMW PAHs could be transported from remote locations.